2017
DOI: 10.1107/s2053230x17015813
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of a pyridoxal 5′-phosphate-dependent aspartate racemase derived from the bivalve mollusc Scapharca broughtonii

Abstract: Aspartate racemase (AspR) is a pyridoxal 5'-phosphate (PLP)-dependent enzyme that is responsible for D-aspartate biosynthesis in vivo. To the best of our knowledge, this is the first study to report an X-ray crystal structure of a PLP-dependent AspR, which was resolved at 1.90 Å resolution. The AspR derived from the bivalve mollusc Scapharca broughtonii (SbAspR) is a type II PLP-dependent enzyme that is similar to serine racemase (SR) in that SbAspR catalyzes both racemization and dehydration. Structural compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…broughtonii Asp racemase, respectively, which are also involved in binding to PLP [50,52], were conserved in these SDHLs at position 309. Taken together, these findings suggested that the binding mode of PLP in these SDHLs was similar to those in SDH, SRR, and Asp racemase of animal origin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…broughtonii Asp racemase, respectively, which are also involved in binding to PLP [50,52], were conserved in these SDHLs at position 309. Taken together, these findings suggested that the binding mode of PLP in these SDHLs was similar to those in SDH, SRR, and Asp racemase of animal origin.…”
Section: Discussionmentioning
confidence: 99%
“…The alignment analysis also suggested differences in the active-site residues of these enzymes. Namely, Ala-222, Gly-239, and Gly-245 residues in rat SDH, rat SRR, and S. broughtonii Asp racemase, respectively, whose backbone carbonyl groups are involved in the interaction with the side chain of the substrate [50][51][52], were conservatively substituted for Ser at position 228, whereas the so-called Asn loop sequence, SXGNX, which surrounds the -carboxy group of the substrate, was conserved in mammalian SDHL between residues Ser-71 and Ala-75 ( Figure 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second key stabilizing feature often found in PLP cofactor binding sites is an aromatic amino acid side chain engaged in a favorable π-π interaction with the pyridine ring. In enzymes such as serine racemase ( Figure 6A ) (Smith et al, 2010 ), aspartate racemase (Mizobuchi et al, 2017 ) ( Figure 6C ) and serine dehydratase ( Figure 6D ) (Wang et al, 2012 ), the aromatic ring for π-stacking is provided by a Phe residue immediately preceding the essential lysine in the primary sequence. The aromatic ring of this Phe side chain is engaged in an edge-to-face π-π-interaction at the si -face of the PLP-ring.…”
Section: Pyridoxal Phosphate Sitementioning
confidence: 99%
“…A survey of current PLP-dependent racemase structures in the pdb shows that, in fact, these enzymes feature a broad range of proton donors for the pyridine ring. In aspartate racemase (Mizobuchi et al, 2017 ), Cys321 serves as H-bond donor ( Figure 6C- PDB code: 5YBW), whereas α-amino ε-caprolactam racemase ( Figure 6E- PDB code: 5M46), (Frese et al, 2017 ) and isoleucine 2-epimerase ( Figure 6F -PDB code: 5WYA) (Hayashi et al, 2017 ) utilize aspartatic acid residues Asp238 and Asp250, respectively, as PLP-nitrogen protonating residues. Serine racemase ( Figure 6A– PDB code: 3L6B) (Smith et al, 2010 ) employs a serine residue, Ser313, reminiscent of β-eliminase enzymes such as tryptophan synthase or O-acetylserine sulfhydrylase (OASS).…”
Section: Pyridoxal Phosphate Sitementioning
confidence: 99%